Generic motor tests as tools to identify sports talent: a systematic review - Blena Marinho; Fabrício Vasconcellos Vieira do Amaral; Leonardo Gomes de Oliveira Luz; Guilherme Locks Guimarães; Luiz Alberto Batista; Daniel das Virgens Chagas (Termedia Publishing House, 2024)
Despite motor coordination being an underlying capacity for the execution of sports motor skills, more information is needed if its evaluation can contribute to identifying sports talent. Furthermore, more needs to be known about which types of generic motor tests can predict the future sporting performance of young athletes of different ages. The objective of this study was to evaluate the literature on the use of generic motor tests, which assess levels of general evolution, in identifying young talents in sport. This systematic review was carried out based on the PRISMA protocol, with a search that was undertaken in two stages: an electronic search of studies written in English in PubMed, Science Direct, Web of Science, and SPORTDiscus; and a search directed to articles written in Portuguese and Spanish in the LILACS , IBECS and SciELO databases. Twenty articles were included in the review: 12 cross-sectional, 6 longitudinal, and 2 retrospective. The methodological quality of the studies was assessed based on ST ROBE. No studies were classified as low-quality. The results suggest that generic motor tests may be important in the talent identification process, since the level of motor coordination is associated with sports performance and, as such, is important for performance discrimination and prediction. The predominance of studies analysed adolescents, males, soccer and the KTK (Körperkoordinationstest für Kinder) motor test. It seems plausible to recommend that sports professionals apply the findings of this study in youth sports performance and practice environments.